360-Degree Video Marketing: The Role of Emerging Technologies in Tourism Destination Choice - Rahimizhian, Sima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The use of 360-degree videos in marketing plans allows destination marketers to give a virtual adventure to their customers before their actual trip. Combining the motivation theory and Technology Acceptance Model (TAM), a research approach was developed to examine whether 360-degree videos are influential in creating a more positive attitude and influencing users' behavioral intentions towards a destination. To evaluate the relationships between the proposed constructs, structural equation modeling (SEM) was used. An online survey collected data from European participants (n = 598) regarding Hong Kong as a tourism destination. The results revealed that both intrinsic and extrinsic motivators influence tourists’ satisfaction with a 360-degree experience of the destination that indirectly affects their visit and electronic word of mouth (eWOM) intentions through behavioral involvement. Overall, the findings indicate that a 360-degree video effectively attracts customers and influences their attitudes and behaviors. The research includes theoretical, managerial implications, and guidelines for future studies relying on these results.

ÖZ: 360-derece videoların pazarlama planlarında kullanılması, destinasyon pazarlamacılarının müşterilerine gerçek seyahatlerinden önce sanal bir macera yaşatmalarına olanak tanır. Motivasyon teorisi ve Teknoloji Kabul Modeli (TAM) birleştirilerek, 360-derece videoların daha olumlu bir tutum oluşturmada ve kullanıcıların bir destinasyona yönelik davranışsal niyetlerini etkilemede etkili olup olmadığını incelemek için bir araştırma yapılmıştır. Önerilen yapılar arasındaki ilişkileri değerlendirmek için yapısal eşitlik modellemesi (SEM) kullanılmıştır. Araştırma kapsamında, Avrupalı katılımcılardan (n = 598) turizm destinasyonu olarak Hong Kong ile ilgili verileri toplamak için çevrimiçi anket şeklinde kullanılmıştır. Sonuçlar, hem içsel hem de dışsal motivasyonların, turistin 360 derecelik bir destinasyon deneyimi ile memnuniyetini, dolaylı olarak ziyaretlerini ve davranışsal katılım yoluyla elektronik ağızdan ağıza (eWOM) niyetlerini etkilediğini ortaya koymuştur. Genel olarak, bulgular 360 derecelik bir videonun müşterileri çekmek, onların tutum ve davranışlarını etkilemek için etkili bir araç olduğunu göstermektedir. Araştırma, bu sonuçlara dayanan gelecekteki çalışmalar için teorik, yönetsel çıkarımlar ve yönergeler içermektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Co-Supervisor: Prof. Dr. Mustafa İlkan and Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Thesis Tez; Faculty of Tourism; Tourism--Tourism Destination Choice--Emerging Technologies; 360-degree video; technology acceptance; virtual experience; intrinsic and extrinsic motivators; TAM; tourism destination choice